Who Restores Hip Biomechanics More Effectively after a Femoral Neck Fracture? Comparison of Total Hip Arthroplasties Performed by Either Hip Surgeons or Orthopaedic Residents - Fernando Diaz-Dilernia, MD; Agustin Garcia-Mansilla, MD; Lionel Llano, MD; Martin Buljubasich, MD; Jose Ignacio Oñativia, MD; Pablo Ariel Isidoro Slullitel, MD; Gerardo Zanotti, MD; Fernando Comba, MD; Francisco Piccaluga, MD; Martin Alejandro Buttaro, MD (Arthroplasty Today, 2020)
Background: This study aims to analyze the ability to restore hip biomechanics in patients who undergo total hip arthroplasty for displaced femoral neck fractures operated by either hip surgeons (HSs) or orthopaedic residents (ORs). Methods: We retrospectively compared 95 patients treated by HSs (group A) with 110 patients treated by ORs (group B). Leg-length discrepancy, femoral offset (FO), center of rotation (COR), acetabular inclination, and acetabular anteversion were evaluated on postoperative radiographs using the healthy contralateral hip as control. Results: The median leg-length discrepancy was 2 mm for both groups (P = .74). The leg length was increased in 54% of the HS group and 57% of the OR group (P = .13). The median FO difference of groups A and B were 7 mm and 5.5 mm, respectively (P = .14). FO was increased in 80% of the HS group and 69% of the OR group (P = .19). Median discrepancies of the horizontal and vertical CORs were not statistically relevant, with P-values of .69 and .14, respectively. The horizontal COR was slightly medialized in 58% of the HS group and 53% of the OR group (P = .003). The vertical COR was slightly proximal in 66% of the HS group and 76% of the OR group (P = .28). The median acetabular inclination angles of groups A and B were 41° and 40°, respectively (P = .62). The median anteversion angle was 19° for both groups (P = .89). Conclusions: The horizontal COR was the only measurement with statistical significance. To conclude, ORs under supervision are as reliable as HSs to properly restore hip biomechanics in patients who undergo total hip arthroplasty for displaced femoral neck fractures.